Severe Plastic Deformation an Advanced Method for Nanostructuring Shape Memory Alloys - Gheorghe GURAU (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2007)
Severe plastic deformation (SPD) is an advanced plastic deformation. In this process nanostructuring metals and alloys may be produced. Nanostructured shape memory alloys are associate with a very high strength, toughness, fatigue life and wear resistance. In recent, bulk nanostructured SMA are used for medicine advanced applications and smart micro devices. In this paper we present the concept and principles SPD. There are two distinct methods: Equal Channel Angular Pressing ECAP or Equal Cannel Angular Extrusion –ECAE and High Pressure Torsion – HPT. Also we present some results about nanostructuring a hard deformable shape memory alloy using a original HPT, and a improved ECAE device.